Thalamic gamma oscillations correlate with reaction time in a Go/noGo task in patients with essential tremor. - Brücke, C; Bock, A; Huebl, J; Krauss, J; Schönecker, T; Schneider, G; Brown, P; Kühn, A (2013)
Intracerebral recordings of neuronal activity in patients undergoing deep brain stimulation have revealed characteristic movement-related desynchronization at frequencies <30 Hz and increased activity in the gamma band (~30-100 Hz) in the basal ganglia and thalamus. Thalamic gamma activity is also found during arousal. Here, we explore oscillatory gamma band activity recorded from the ventralis intermedius nucleus of the thalamus during motor performance in a Go/noGo task in 10 patients with essential tremor after implantation of deep brain stimulation electrodes. We show that movement-related gamma activity is lateralized to the nucleus contralateral to the moved side similar to previous findings in the globus pallidus internus and the subthalamic nucleus. The onset of contralateral gamma band synchronization following imperative Go cues is positively correlated with reaction time. Remarkably, baseline levels of gamma activity shortly before the Go cue correlated with the reaction times. Here, faster responses occurred in patients with higher levels of pre-cue gamma activity. Our findings support the role of gamma activity as a physiological prokinetic activity in the motor system. Moreover, we suggest that subtle fluctuations in pre-cue gamma band activity may have an impact on task performance and may index arousal-related states.